A colorimetric and "off–on" fluorescent Pd2+ chemosensor based on a rhodamine-ampyrone conjugate: synthesis, experimental and theoretical studies along with in vitro applications. (6th February 2019) - Mondal, Sanchita; Manna, Saikat Kumar; Pathak, Sudipta; Masum, Abdulla Al; Mukhopadhyay, Subrata
Abstract : We successfully designed and developed a rhodamine based "turn-on" chemosensorL for the detection of Pd 2+ ions down to 1.19 × 10 −5 M (11.9 μM). Abstract : We successfully designed and developed a rhodamine based "turn-on" chemosensorL for the detection of Pd 2+ ions down to 1.19 × 10 −5 M (11.9 μM). In organo-aqueous solution, probeL displayed highly selective and sensitive colorimetric and fluorescence responses toward Pd 2+ based on the ring-opening mechanism of the rhodamine spirolactam ring upon complexation with Pd 2+ . In the presence of Pd 2+ ions, probeL formed anL –Pd 2+ complex in 1 : 1 stoichiometry which was confirmed by the Job plot and mass spectroscopy. Moreover, we performed DFT (density functional theory) studies to identify the coordination characteristics and binding nature ofL and theL –Pd 2+ complex. In addition, cell imaging experiments revealed that probeL was able to permeate cells, and able to image Pd 2+ in living cells.